PRODUKSI COMMERCIAL GRADE FURFURAL DARI TONGKOL JAGUNG DALAM MENUNJANG AGROINDUSTRI NASIONAL - Suharto Suharto; Susanti Sundari (Fakultas Teknik Universitas Tulang Bawang Lampung, 2022)
Furfural as one of the strategic chemicals, especially in the petroleum industry (oil refineries) has a fairly wide market opportunity. Up to now, there is no furfural factory in Indonesia. The development of furfural industry technology can be used as the forerunner to the establishment of a national furfural factory. The development of furfural industry technology from corn cobs can also increase the added value of corn cobs while reducing environmental problems. Research Methodology in Furfural Manufacturing Process consists of Process Selection, preparation of raw materials, hydrolysis and dehydration processes, as well as yield and purification stages. The outputs that have been obtained from initial and further research are a Digester Prototype with a capacity of 1000 L along with its platform and a stripper column with a reboiler capacity of 60 L, a product in the form of crude furfural with a purity of 94% which is ready for the purification process, a shelter with a size of 4 x 9 m2 which is in Inside there is a steam generator, digester and stripper column and a vacuum distillation column with a reboiler capacity of 60 L and a column height of 200 cm. If viewed from the calculation of the gross profit margin on a basis of 1 ton of furfural, the establishment of a furfural factory can be said to be interesting for further study